EVALUATION OF THE QUR’AN READING AND WRITING PROGRAM (BTQ) USING THE CIPP MODEL AMONG STUDENTS AT MANGGARUPI ELEMENTARY MADRASAH - Nur Said Mutakhir; Sitti Mania; Muhammad Nur Akbar Rasyid (PT Altin Riset Publishing, 2026)
This study aims to evaluate the Al-Qur'an Reading and Writing Program (BTQ) implemented at Madrasah Ibtidaiyah Manggarupi using the CIPP (Context, Input, Process, Product) evaluation model. This evaluation was conducted to determine the extent to which the BTQ program was able to improve students' Al-Qur'an literacy skills and the effectiveness of its implementation in the context of religious education at the madrasah. The research method used was descriptive qualitative with data collection through interviews, observations, and document analysis. Research informants included educators in charge of the program, teaching staff, students, and parents of students. The results of the evaluation on the context component showed that the BTQ program was a school initiative driven by the needs of students who still had low Al-Qur'an reading and writing skills and the support of the school's vision that emphasized religious values. In the input component, it was found that most of the teaching staff came from classroom educators with a background in religious education, but special BTQ training was still limited, and supporting facilities and infrastructure such as mushafs and digital learning media were still inadequate. The learning process runs according to schedule with various methods, but the constraints of time constraints and the large number of students affect the effectiveness of individual supervision and evaluation. The products of this program show significant improvement, with 70% of students being able to read the Qur'an properly and correctly according to basic tajwid rules and increasing positive religious attitudes. This study recommends strengthening teacher training, developing curriculum and learning methods, and improving facilities and infrastructure to support the sustainability and quality improvement of the BTQ program at Madrasah Ibtidaiyah.